A postbiotic from Aspergillus oryzae attenuates the impact of heat stress in ectothermic and endothermic organisms - Kaufman, J. D. (2021)
Fil: Kaufman, J. D. University of Tennessee. Department of Animal Science. Knoxville, USA.